1998
DOI: 10.1046/j.1365-4362.1998.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

A questionnaire study of road pavers’ and roofers’ work‐related skin symptoms and bitumen exposure

Abstract: Roofers endure greater exposure to chemicals than road pavers. Certain components, e.g. polycyclic aromatic hydrocarbons in bitumen, can be absorbed through the skin. Skin exposure should be lowered by keeping the tools, working clothes, shoes, and gloves clean. Overalls and gloves are recommended to be changed at least once a week. Water laundering is not sufficient in dissolving bitumen from overalls and underwear. Cleaning the skin with solvents or naphtha is not recommended, as they are skin irritants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…12 In a previous study among Finnish workers, skin irritation was reported by 44% of the roofers and 31% of the road pavers who worked with bitumen. 54 However, no studies have thus far looked into the relationship between skin burn and levels of biomarkers of exposure in roofers. In our analyses, the existence of skin burn was an important predictor of PAH biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…12 In a previous study among Finnish workers, skin irritation was reported by 44% of the roofers and 31% of the road pavers who worked with bitumen. 54 However, no studies have thus far looked into the relationship between skin burn and levels of biomarkers of exposure in roofers. In our analyses, the existence of skin burn was an important predictor of PAH biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Bitumens are dark solid or semisolid materials predominantly composed of asphaltenes, straight and branched aliphatic hydrocarbons, naphthene aromatics and resins. Some types of bitumen may contain higher levels of PAH 20 with lipophilic characteristics that could alter the skin hydrolipid film and cause disease 21 …”
Section: Discussionmentioning
confidence: 99%
“…In vivo and in vitro studies have demonstrated that bitumen products can induce irritant and allergic contact dermatitis in humans 21 and moderate hyperkeratosis and epidermal hyperplasia in rats 22 . Bitumen products may alter skin barrier integrity 23 by denaturation of keratin and other epidermal proteins, removal of superficial lipids, surfactant transport to the upper epidermal layers, cell membrane damage and direct cytotoxicity 24 …”
Section: Discussionmentioning
confidence: 99%
“…Von den Straßenbauarbeitern gaben 22% an, oft oder manchmal an �Dermatitis" zu leiden, im Fall der befragten Dachdecker lag der Anteil bei 15%. Als Ursachen für diese gesundheitlichen Probleme wurden von den Betroffenen jedoch nicht nur heißes und kaltes Bitumen angeschuldigt, sondern beispielsweise auch künstliche Mineralfasern (Dachdecker) oder Amin-haltige Produkte (Straßenbauarbeiter) (Riala et al 1998). Eine Fallbeschreibung befasst sich mit einem Mann, der einen Monat nach versehentlichem Hautkontakt mit kaltem Flüssigbitumen ("cutback", Lösungsmittel: Toluol und Benzin) im Gesicht diskoiden Lupus erythematodes entwickelte.…”
Section: Wirkung Auf Haut Und Schleimhäuteunclassified